2016
DOI: 10.1074/jbc.r114.635995
|View full text |Cite
|
Sign up to set email alerts
|

Human Enteroids/Colonoids and Intestinal Organoids Functionally Recapitulate Normal Intestinal Physiology and Pathophysiology

Abstract: Identification of Lgr5 as the intestinal stem cell marker as well as the growth factors necessary to replicate adult intestinal stem cell division has led to the establishment of the methods to generate "indefinite" ex vivo primary intestinal epithelial cultures, termed "mini-intestines." Primary cultures developed from isolated intestinal crypts or stem cells (termed enteroids/ colonoids) and from inducible pluripotent stem cells (termed intestinal organoids) are being applied to study human intestinal physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
243
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 249 publications
(249 citation statements)
references
References 63 publications
(36 reference statements)
4
243
1
1
Order By: Relevance
“…Is Reproducible Across HIEs from Different People. HIEs are novel, physiologically active, nontransformed cultures that are increasingly used to study human pathogen-host interactions (5,8,9,39,40). We first evaluated the variability in the transcriptional response to HRV infection in HIEs by analyzing transcriptomes from one jejunal HIE culture by microarray analysis.…”
Section: Significancementioning
confidence: 99%
“…Is Reproducible Across HIEs from Different People. HIEs are novel, physiologically active, nontransformed cultures that are increasingly used to study human pathogen-host interactions (5,8,9,39,40). We first evaluated the variability in the transcriptional response to HRV infection in HIEs by analyzing transcriptomes from one jejunal HIE culture by microarray analysis.…”
Section: Significancementioning
confidence: 99%
“…In vitro models (e.g., human colon cancer cells) may not recapitulate normal tissue architecture, biology, or molecular signaling events (13,16,17,19), while in vivo models, such as suckling mice (20) and ileal loops (21), are labor-intensive and not suited to high-throughput screening. These considerations underscore the need for models of intestinal signaling and secretion which are compatible with high-throughput analyses and recapitulate the pathophysiology of ST-induced diarrhea (2,16,17,22,23).…”
mentioning
confidence: 99%
“…Stem cells isolated from mouse or human intestinal crypts are propagated in three-dimensional cultures, where they form "miniguts," encompassing the cell types of the mature intestinal epithelium and recapitulating normal intestinal physiology (16,17,24). While enteroids are biologically relevant models for infectious diarrheal diseases (16,17,22,23), their suitability as a platform to study ST-induced intestinal secretion remains unknown (17). Since previous studies demonstrated that pharmacological agents, including complex multimeric proteins like cholera toxin, readily access the lumen of enteroids (25,26), we predicted that these organoids should respond to GUCY2C ligands.…”
mentioning
confidence: 99%
“…To date, human enteroids have been shown to model human rotavirus (RV) infection, cholera toxin effect on transport, and several aspects of enterohemorrhagic Escherichia coli-related human diarrhea. RV replicates and produces infectious viruses in human enteroids and organoids, with viral replication increasing over 96 h [38].…”
Section: Organoid Disease Modeling and Transplantationmentioning
confidence: 99%